Worldwide reach of short selling regulations - Jain, Archana; Jain, Pankaj K.; McInish, Thomas H.; McKenzie, Michael (Journal of Financial Economics, 2013)
We characterize legality and incidence of short selling in a worldwide, multimarket framework. Home country short selling restrictions curtail home market stock borrowing by 45% and reduce short selling of the country's American Depository Receipts (ADRs) by 68% due to regulatory reach. Also, the 2008 US ban on short selling of financial firms reduced borrowing in foreign locations. These findings are robust to controls for option availability, enforcement, returns, firm size, trading volume, dividends, ADR level, volatility, days-to-cover, and industry sector. Further, we show that investor conduct resulting from adherence to professional standards is a more powerful mechanism of regulatory reach than intergovernment cooperation.